Peran Aturan Hukum dalam Menciptakan Tata Pemerintahan yang Membangun Partisipasi Demokratis yang Berkelanjutan - Nurfadilla, Yunita; Sahyana, Yana (Jurnal Pemerintahan dan Politik, 2024)
This study analyzes the crucial role of legal rules in creating a governance framework that promotes sustainable democratic participation. Through qualitative research methods and literature review, this research highlights that legal rules establish a legal framework governing the formulation, implementation, and oversight of public policies, ensuring orderliness in political decision-making processes and enforcing government accountability. The findings demonstrate that legal rules play a vital role in upholding good governance, sustainable democracy, and the achievement of broader development goals, including human rights protection and sustainable development. In the context of Indonesia, strengthening the power of legal rules and effective law enforcement are key to achieving good governance and sustainable democracy.